2014
DOI: 10.1063/1.4884075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrostatic and localized plasmon induced light enhancement in hybrid InGaN/GaN quantum wells

Abstract: The light enhancement phenomena in InGaN/GaN multi-quantum wells (MQWs) infiltrated with metal nanoparticles (NPs) are studied using resonant and off-resonant localized plasmon interactions. The emission and recombination characteristics of carriers in InGaN/GaN MQW structures with inverted hexagonal pits (IHPs) are modified distinctly depending on the nature of their interaction with the metal NPs and with the pumping and emitted photons. It is observed that the emission intensity of light is significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, in a light emitter system where the radiative recombination rate is higher, such as that induced by resonant plasmonic nanoparticles, the influence due to image charge is weaker as the speed of the drift and diffusion toward the metal nanoparticles is significantly slower than the e–h recombination rate. 35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a light emitter system where the radiative recombination rate is higher, such as that induced by resonant plasmonic nanoparticles, the influence due to image charge is weaker as the speed of the drift and diffusion toward the metal nanoparticles is significantly slower than the e–h recombination rate. 35…”
Section: Resultsmentioning
confidence: 99%
“…This electrostatic force has a longer range compared to that of the surface plasmonic field that decreases exponential away from the metal–dielectric interface. However, in a light emitter system where the radiative recombination rate is higher, such as that induced by resonant plasmonic nanoparticles, the influence due to image charge is weaker as the speed of the drift and diffusion toward the metal nanoparticles is significantly slower than the e–h recombination rate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the electrostatic properties of metal NPs can enhance the IQE through the image charge effect of metal NPs, and one of the characteristics of this effect is the increased PL lifetime. 27,28 With LSPR of the GaN/Ag system far detuned from the QW emission wavelength (see Fig. 3), and with the increased PL lifetime, the image charge effect is expected to be the cause behind the observed PL enhancement.…”
Section: Effect Of Ag Nanoparticlesmentioning
confidence: 99%
“…Fortunately, Au nanoparticles (NPs) have the capacity to improve the performances of optoelectronic devices [5], [6], owing to their superior ability to modify the optical, electrical, and thermal properties of the surrounding medium. Au NPs can interact with resonant photons through localized surface plasmon resonance (LSPR) [7], [8], thus exhibiting a remarkably enhanced response in surface-enhanced Raman spectroscopy [9], [10] and photoluminescence spectroscopy [11], [12]. In addition, the work function difference between Au and Ge, as well as the electrostatic effect of image charges in Au NPs, can modify the energy band below the Au NP/Ge interface, thus modulating the electronic transport and light-matter interaction in Ge.…”
mentioning
confidence: 99%